2021
DOI: 10.1038/s41598-021-92696-w
|View full text |Cite
|
Sign up to set email alerts
|

Annual climatic fluctuations and short-term genetic variation in the eastern spadefoot toad

Abstract: In addition to variations on the spatial scale, short- and long-term temporal variations, too, can impose intense selection on the overall genetic diversity and composition of a population. We hypothesized that the allelic composition in populations of the eastern spadefoot toad (Pelobates syriacus) would change among successive years in accordance with the short-term changes in environmental conditions. Surprisingly, the effect of short-term climate fluctuations on genetic composition have rarely been address… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 46 publications
(52 reference statements)
1
2
0
Order By: Relevance
“…Our results are in line with those of other recent other studies and reviews that have provided evidence of an association between genetic structure and the environment (e.g., Schmidt and Anderson, 2006;McCairns and Bernatchez, 2008;Ortego et al, 2012;Stojak et al, 2019). Further support for an environmental effect on microsatellite variation comes from the study by Cohen et al (2021), which revealed a significant correlation between climatic variation among successive years, primarily the amount of rainfall and number of rainy days, and both microsatellite allelic composition and diversity (15% of the total explained genetic variance). Cohen et al (2021) sampled seven rain pools, which we also sampled for the present study, making their earlier study's results highly relevant.…”
Section: Natural Selectionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our results are in line with those of other recent other studies and reviews that have provided evidence of an association between genetic structure and the environment (e.g., Schmidt and Anderson, 2006;McCairns and Bernatchez, 2008;Ortego et al, 2012;Stojak et al, 2019). Further support for an environmental effect on microsatellite variation comes from the study by Cohen et al (2021), which revealed a significant correlation between climatic variation among successive years, primarily the amount of rainfall and number of rainy days, and both microsatellite allelic composition and diversity (15% of the total explained genetic variance). Cohen et al (2021) sampled seven rain pools, which we also sampled for the present study, making their earlier study's results highly relevant.…”
Section: Natural Selectionsupporting
confidence: 93%
“…Further support for an environmental effect on microsatellite variation comes from the study by Cohen et al (2021), which revealed a significant correlation between climatic variation among successive years, primarily the amount of rainfall and number of rainy days, and both microsatellite allelic composition and diversity (15% of the total explained genetic variance). Cohen et al (2021) sampled seven rain pools, which we also sampled for the present study, making their earlier study's results highly relevant. However, explaining our results according to the natural selection hypothesis is currently controversial, as most microsatellite loci in the genome are generally thought to be neutral, with allele length changing due to drift.…”
Section: Natural Selectionmentioning
confidence: 99%
See 1 more Smart Citation